Black-foot disease of grapevine: an update on taxonomy, epidemiology and management strategies - AGUSTÍ-BRISACH, Carlos; ARMENGOL, Josep (Phytopathologia Mediterranea, 2013)
Black-foot is one of the most destructive grapevine trunk diseases in nurseries and young vineyards, causing necrotic root lesions, wood necrosis of the rootstock base, and a gradual decline and death of grapevines. Causal agents of the disease are included into the genera Campylocarpon, “Cylindrocarpon”, Cylindrocladiella and Ilyonectria. Recent taxonomical studies of Neonectria and related genera with “Cylindrocarpon”-like anamorphs based on morphological and phylogenetic studies, divided Neonectria into five genera. Thus, the current taxonomical position and classification of the causal agents of black-foot disease, mainly “Cylindrocarpon”/Ilyonectria, comprises one of the main topics of this review. The review also provides an update on geographical distribution, epidemiology and management strategies of the disease.